PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR FISIKA DITINJAU DARI MOTIVASI BELAJAR PADA MATERI ELASTISITAS DAN HUKUM HOOKE SISWA KELAS X SMA YPPK YOS SUDARSO MERAUKE - Saragih, Elly Avida (Jurnal Ilmu Pendidikan Indonesia, 2016)
It had been researched about The Influence of Discovery Learning of Learning Process Model toward the Physics Learning Result Observed on The Learning Motivation in Elasticity Materials and Hooke Law of The Tenth Class Students of SMA YPPK Yos Sudarso Merauke. The research results show (1) there is the influence of discovery learning r = 0.933, whereas the number of Discovery Learning of Learning Process Model contribution r square = 87.1% and the rest 12.9% determined by unstudied other cause. (2) there is the influence of learning motivation toward the learning result of the tenth class students of SMA YPPK Yos Sudarso Merauke in Elasticity Materials and Hooke Law r = 0.362, whereas the number of students learning motivation contribution r square = 13.1% and the rest 86.9% determined by unstudied other cause. (3) there is the influence of discovery learning of learning process model and the learning motivation toward the learning result of the tenth class students of SMA YPPK Yos Sudarso Merauke in Elasticity Materials and Hooke Law r = 0.934 whereas the number of learning process model contribution towards the learning result of the tenth class students of SMA YPPK Yos SudarsoMerauke in Elasticity Materials and Hooke Law jointly r square = 87.2% and the rest 12.8% determined by unstudied other cause. Key Words: Discovery Learning of Learning Process Model, Students Motivation Learning,Learning Result in Elasticity Materials and Hooke Law.